The Islamic built environments perception in Malaysia - Mohd Isa, Norliza (IIUM Press, 2011)
The main purpose of this paper is to highlight the issues regarding the Islamic built environment in Malaysia. Because Islam is the nation's majority religion, the government of Malaysia strives to adopt Islamic values in its regulation of Malaysia's built environment. Yet, given Malaysia's multi-racial and multi-religious lifestyle, how can an Islamic-based, built environment playa role there? Have Islamic concepts been implemented correctly and appropriately in the construction of Malaysia's cities? This research is based on the assumption that the desire to inject Islamic values into Malaysia's built environment for the purpose of providing an Islamic identity to the nation can clearly be seen from the architectural, landscape and planning approaches that have been deployed by the professionals (those who are relevantly related in the decision-making process of city development and design concepts include administrators, architects, planners and engineers). This ongoing research employs descriptive and survey-based research designs rooted in qualitative and quantitative research paradigms. The research method implemented is a Delphi method that uses structured and semi-structured interviews for primary data collection to achieve the objectives of this research include (1) to define the perceptions of experts from a variety of races and religions on the subject of Islamic built environments in order to ensure the appropriate implementation of the concept in Malaysian contexts; and (2) to evaluate and analyze the findings with regard to the degree to which the study area in Putrajaya are truly Islamic cities and are compatible with the criteria associated with an Islamic built environment in Malaysia. This research anticipates coming out with the characteristics of an Islamic built environment based on the input of "experts" and suggestions regarding how professionals can use these perceptions as guidance to concretely act on the design process.